Optimization of parabolic photovoltaic and solar thermal tracker model systems using heat transfer fluid - Satria, Habib; Maizana, Dina; Dayana, Indri (Institute of Advanced Engineering and Science, 2025)
Renewable energy sources such as photovoltaic (PV) and solar thermal (T) used in tropical Indonesia are still not optimal in converting electrical energy. This is caused by the movement of the sun which is not centered on the surface of the photovoltaic/thermal (PV/T). Based on this, PV/T technology was developed with a parabolic tracker system combined with T control with the aim of optimizing electrical energy conversion. The testing technique was carried out using an experimental method by comparing the installation of PV/T technology with a parabolic tracker system and a flat PV position. In the PV/T parabolic tracker, the supporting components use aluminum foil technology and heat transfer fluid (HTF) to reduce excess heat on the panel surface. The parabolic tracker system is implemented through a centralized system following the sun and aluminum foil and HTF technology function to keep the surface temperature stable. The results of PV performance testing at peak loads carried out at 10:00 am-3:00 pm, the installation of flat PV produced an average DC power of 71.68 Wp and the parabolic tracker system produced an increase in average DC power of 84.57 Wp, while with an increase in power of 17.98% during fluctuating weather conditions.